DESCRIPTION OF SGPT (SERUM GLUTAMIDE PERUVIT TRANSAMINASE) LEVELS IN ACTIVE SMOKER PATIENTS AT HORAS INSANI PEMATANGSIANTAR HOSPITAL - Mareny , Riada; Alexander, Alexander; Wardati, Jumadiah; Sihombing, Eka; Nurmala, Nurmala; Mazdalifah, Nur (International Conference on Health Science, Green Economics, Educational Review and Technology, 2021)
Smoking has become a habit for some people in their daily lives because they follow the lifestyle of the surrounding environment. There are three dangerous substances that are most dominant in cigarettes, namely nicotine, tar and carbon monoxide. When smoking, these chemicals enter the body and if this continues continuously can cause liver damage, thereby increasing SGPT levels. This study aims to describe SGPT levels in active smokers at Horas Insani Hospital, Pematangsiantar. The research design used is descriptive. The population in this study were all active smokers at Horas Insani Pematangsiantar Hospital, totaling 36 active smokers. The number of samples in this study were 30 active smokers taken by purposive sampling. The variable in this study was SGPT levels in active smokers. SGPT level examination technique with the Kinetic-IFCC method. Data analysis was obtained through editing, coding and tabulating then analysis of SGPT levels was analyzed in percentage form. Of the 30 respondents on the results of the study it can be concluded that 21 respondents (70%) were active smokers at Horas Insani Hospital Pematangsiantar, had SGPT levels increased> 35 U/L.